Synthesis and characterization of structure and magnetic properties of ferrite nanoparticles prepared by thermal treatment method - Naseri, Mahmoud Goodarz (2012)
Spinel ferrite nanocrystals are regarded as one of the most important inorganic nanomaterials because of their electronic, optical, electrical, magnetic, and catalytic properties. These properties are dependent on the chemical composition and microstructural characteristics in which the particle size and shape might be controlled in the fabrication processes. The preparation of spinel ferrite nanocrystals through different routes has become an essential in research and development. But,the most commonly applied synthesis methods are difficult to employ on a large scale because of their complicated procedures, high reaction temperatures, long reaction times, toxic reagents and by-products, and their potential harm to the environment. In this thesis a simple thermal treatment method is described for synthesis of spinel ferrite MFe2O4 (M = Ni, Co, Mn, Zn, or their binary metal) nanoparticles. In this method, an aqueous solution of poly (vinyl pyrrolidone) (PVP was prepared by dissolving the polymer in deionized water at 343 K before adding iron nitrate and respective metal nitrates and constantly stirring at 353 K for 2 h. The dissolved solution was heated until dried at 353 K for 24 h on a glass Petri dish. The solid and orange coloured transparent remains were crushed and ground in a mortar to form powder before calcinations at different temperatures for 3 h to decompose organic matters and crystallized the ferrite nanparticles. We concluded that the effect and role of PVP in the synthesis of cobalt ferrite nanoparticles by the thermal treatment method is astonishing. Briefly, as was discussed when we considered our XRD results, TEM images, and FT-IR spectra, PVP plays four crucial roles in synthesizing cobalt ferrite nanoparticles, i.e., (1) the control of the growth of the nanoparticles by varying the concentration of PVP; (2) the prevention of agglomeration of the nanoparticles; (3) the enhancement of the degree of the crystallinity of the nanoparticles, and (4) the production of nanoparticles that have a uniform distribution of shapes. Thermo-gravimetry analyses was used to estimate a range of calcination temperature where the polymer mass loss started at 678 K and has the maximum decomposition at 778 K. The optimum calcination temperature was confirmed by Fourier transform infrared spectroscopy (FTIR) measurement by the presence of metal oxide bands at all temperatures and the absence of organic bands at 723 and 823 K for NiFe2O4 and CoFe2O4 nanoparticles and at 873 K for,MnFe2O4, ZnFe2O4 and Nix Co1-x Fe2O4 nanoparticles. The transmission electron microscopy (TEM) images showed cubical spinel ferrite nanoparticles that were uniform in both morphology and particle size distribution. The x-ray diffraction (XRD) diffraction patterns showed crystalline phases that confirmed the formation of nanocrystalline single-phase spinel ferrite nanoparticles with a face-centered cubic structure, common structure for nanomaterials. The average particle sizes were determined from TEM images and found the particle size increased with the calcinations temperature from 7 to 47 nm for NiFe2O4, from 12.5 to 39 for CoFe2O4,from 12 to 22 nm for MnFe2O4, from 17 to 31 nm for ZnFe2O4 and from 14 to 25 nm for Nix Co1-x Fe2O4 nanoparticles. These sizes are in a good agreement with XRD results. The magnetic properties were determined by vibrating sample magnetometer (VSM),which showed that the calcined samples exhibited ferromagnetic, ferromagnetic or superparamagnetic behaviors. The VSM results displayed ferromagnetic behaviors for NiFe2O4, CoFe2O4, and Nix Co1-x Fe2O4 nanoparticles and super paramagnetic behaviors for MnFe2O4 and ZnFe2O4 nanoparticles. The magnetic properties acquired by VSM, such as saturation magnetization and coercivity field are dependent on the calcination temperatures. The magnetic properties were also confirmed by the use of electron paramagnetic resonance (EPR) spectroscopy, which revealed the existence of unpaired electrons and also measured peak-to-peak line width (ΔHpp), resonant magnetic field (Hr), and the g-factor for MnFe2O4 and ZnFe2O4 nanoparticles while NiFe2O4, CoFe2O4, and Nix Co1-x Fe2O4 nanoparticles did not exhibit resonance signal. This could be possibly due to the super exchange interaction produces that occurs in these nanoparticles. Our results show that we have succeeded in fabricating crystalline NiFe2O4,CoFe2O4, MnFe2O4, ZnFe2O4 and Nix Co1-x Fe2O4 nanoparticles by a simple thermal treatment method. This method is cost-effective, environmentally-friendly, has low reaction temperatures, and produced no by-product effluents. It can be extended to fabricating other spinel ferrite nanoparticles of interest or other metallic oxides nanocrystals.